Preserving Batik Trusmi’s image: Public relations strategies in Cirebon’s heritage - Anwar, Rully Khairul; Lusiana, Elnovani; Khadijah, Ute Lies Siti; Kusmayadi, Ika Merdekawati (Universitas Padjadjaran, 2024)
Background: Batik, as an Indonesian art form, has not only evolved but also adapted to present needs while maintaning its cultural roots. Moreover, the current surge in batik sales brings both benefits and challenges for artisans. Purpose: The study examines public relations strategies aimed at enhancing Batik’s image, promoting cultural heritage, and supporting the local economy. Methods: This study employed the social constructivism approach to gain insight into the cultural heritage of Trusmi Batik. The research methodology encompassed the use of observation, interviews, and documentation as techniques to thoroughly comprehend the subject matter. Results: Trusmi Village, renowned for its distinctive batik art, has transformed into a popular shopping center and tourist hotspot. The batik industry seeks to boost household income and capitalize on its proximity to transportation routes. This expansion has not only generated new employment opportunities but has also inspired ventures beyond the field. Additionally, government support and the role of social media in corporate communications have played crucial roles in contributing to the success of Trusmi. Conclusion: The batik industry in Trusmi has brought about a transformation in the region, providing job opportunities and fostering economic prosperity for entrepreneurs and the overall economy. Government investments in branding and the role of social media have played significant roles in contributing to its growth. Additionally, community efforts have resulted in economic benefits, population growth, and advantages in terms of tourism. Implications: The growth of the Trusmi Batik industry holds significant implications, highlighting the significance of promoting cultural heritage and storytelling. Furthermore, it contributes to economic progress, social cohesion, and community ties. Government assistance is paramount in ensuring the enduring sustainability and expansion of the sector.